Incretins modulate progesterone biosynthesis by regulating bone morphogenetic protein activity in rat granulosa cells. Issue 178 (April 2018) - Nishiyama, Yuki; Hasegawa, Toru; Fujita, Shiho; Iwata, Nahoko; Nagao, Satoko; Hosoya, Takeshi; Inagaki, Kenichi; Wada, Jun; Otsuka, Fumio
Highlights: Incretins, GIP and GLP-1, suppressed FSH-induced progesterone synthesis by rat granulosa cells. GIP, but not GLP-1, treatment enhanced BMP-induced Smad1/5/8 activation by granulosa cells. BMP-6 suppressed the receptor expression of GIP, but not that of GLP-1, on granulosa cells. GIP modulates ovarian steroidogenesis by upregulating BMPR signaling in granulosa cells. Abstract: The effects of incretins on ovarian steroidogenesis have not been clarified. In this study, we investigated the effects of incretins, including GIP and GLP-1, on ovarian steroidogenesis using rat primary granulosa cells. Treatment with incretins significantly suppressed progesterone synthesis in the presence of FSH, and the effect of GIP was more potent than that of GLP-1. In contrast, incretins had no significant effect on estrogen synthesis by rat granulosa cells. In accordance with the effects of incretins on steroidogenesis, GIP and GLP-1 suppressed the expression of progesterogenic factors and enzymes, including StAR, P450scc, 3βHSD, but not P450arom, and cellular cAMP synthesis induced by FSH. In addition, incretins moderately increased FSHR mRNA expression in granulosa cells. Of note, treatment with GIP, but not treatment with GLP-1, augmented Smad1/5/8 phosphorylation and transcription of the BMP target gene Id-1 induced by BMP-6 stimulation, suggesting that GIP upregulates BMP receptor signaling that can inhibit FSH-induced progesterone synthesis in rat granulosa cells. On the other hand, BMP-6 treatment suppressed the expression of GIP receptor but not that of GLP-1 receptor. Expression of the BMP type-I receptor ALK-3 was upregulated by treatment with GIP and GLP-1 and that of ALK-6 was also increased by GIP, while inhibitory Smad6 expression was impaired by GIP and GLP-1 in rat granulosa cells. Collectively, the results indicate that incretins, particularly GIP, impair FSH-induced progesterone production, at least in part, by upregulating BMP signaling in rat granulosa cells. The modulatory effects of incretins on endogenous BMP activity may be applicable to treatment of dysregulated steroidogenesis such as polycystic ovary syndrome.